Prosody, priming and particular constructions: The patterning of English first-person singular subject expression in conversation - Torres Cacoullos, Rena; Travis, Catherine E. (Journal of pragmatics, 2014)
•Unexpressed (“null”) 1sg subjects occur systematically in English conversation.•There are two loci of variation: absolute initial prosodic position and and-coordinated verbs.•The oft-reported cross-linguistic subject continuity constraint has no independent effect.•Priming is strong, such that a previous coreferential unexpressed subject favors unexpression.•Particular and-coordinating constructions with go and say shape local patterns. Unexpressed subjects, though rare, do occur systematically in English. In this study, we seek to answer the question of what motivates speaker choice between expressed and unexpressed first singular subjects (i.e. I vs. an unexpressed, or null, pronoun) in a corpus of conversational American English. We find that the apparently widespread cross-linguistic constraint of subject continuity is bound to coreferential coordinating constructions with and, including lexically particular constructions ([I Verb1sgiand Ø Quotative verb1sgi], [I go1sgiand Ø Verb1sgi]), and to an overarching priming constraint, whereby coreferential unexpressed mentions tend to cluster together. A pivotal restriction is prosodic, such that, outside of coordinating constructions, unexpressed 1sg subjects occur only in Intonation-Unit initial position. We therefore find that variable I expression is sensitive to factors operative in subject expression in other languages and in language variation more generally, though paramount are prosodic considerations and particular constructions that may be specific to English.